Age-related trends of ischemic sudden cardiac death in women - Hookana, I.; Eskuri, M.A.E; Holmström, L.; Vähätalo, J.; Kenttä, T.; Tikkanen, J.T.; Pakanen, L.; Perkiömäki, J.; Huikuri, H.V.; Junttila, M.J. (International journal of cardiology, 2024)
•After the age of 60, most sudden cardiac deaths (SCD) in women are ischemic origin.•The clinical profile of ischemic SCD in women is age-dependent.•Overweight is more common among younger women with SCD.•Myocardial scars and fibrosis are more common in older ischemic SCD subjects.